Impact of Diet and Exercise Interventions on Glycemic Control and Weight Management in Adults with Type 2 Diabetes: A Systematic Review of Randomized Controlled Trials and Observational Studies - Sikandar, Muhammad Muaaz; Tanvir, Namra; Qadir, Ali; Abdussalam,; Shehzadi, Iqra; Abbas, Ghulam (Indus Journal of Bioscience Research, 2024)
Background: Type 2 diabetes mellitus (T2DM) is a chronic metabolic condition characterized by insulin resistance and impaired insulin production, leading to high blood glucose levels. It is the most common form of diabetes, accounting for 90%-95% of all cases globally. With an increasing prevalence of T2DM, effective management strategies are crucial to control glycemic levels and prevent associated complications. Diet and exercise are considered key interventions to improve glycemic control and manage weight in individuals with T2DM. Objective: This systematic review aims to evaluate the effects of diet and exercise interventions on glycemic control and weight management in adults with Type 2 diabetes. The review focuses on the impact of various diet plans, including low-carbohydrate and Mediterranean diets, as well as different exercise regimens. Methodology: A comprehensive search of randomized controlled trials (RCTs) and observational studies was conducted to identify research on the effects of diet and exercise interventions in managing T2DM. Studies assessing glycemic control (e.g., HbA1c levels) and weight loss outcomes were analyzed to determine the effectiveness of these interventions. Results: The review found that both diet and exercise interventions led to significant improvements in glycemic control and weight management. Low-carbohydrate diets and Mediterranean diets, in particular, demonstrated positive effects on blood glucose levels and insulin sensitivity. Regular physical activity, especially aerobic and resistance exercises, also contributed to improved glycemic control and weight reduction. Conclusion: Diet and exercise interventions are effective strategies for managing Type 2 diabetes, improving both glycemic control and weight management. Incorporating tailored diet plans and exercise regimens into clinical practice may significantly benefit individuals with T2DM. Further studies are needed to refine intervention protocols and address barriers to patient adherence.